2022
DOI: 10.1109/jphot.2022.3165036
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Carrier Injection in AlGaN-Based Deep Ultraviolet Light-Emitting Diodes by Polarization Engineering at the LQB/p-EBL Interface

Abstract: The external quantum efficiency (EQE) of AlGaNbased deep ultraviolet light-emitting diodes (DUV LEDs) is still far from satisfactory due to the main issues of electron leakage and insufficient hole injection. The positive sheet charges generated by polarization at the interface between the last quantum barrier (LQB) and the p-type electron blocking layer (p-EBL) can induce electron accumulation and hole depletion in the vicinity of this interface, leading to electron leakage and hindering the hole injection. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Consequently, it may significantly compromise both the electron blocking and hole injection processes, ultimately resulting in a diminished optical power and efficiency [22]. As a result, many strategies aimed at improving the amount of droop utilize either an Al composition gradient [23][24][25] or a final barrier with a different thickness [23,26,27] as a workaround for this issue. In a previous study we reported high−performance green LEDs employing heterojunction−type last quantum barrier layers [28].…”
Section: Device Structure and Parametersmentioning
confidence: 99%
“…Consequently, it may significantly compromise both the electron blocking and hole injection processes, ultimately resulting in a diminished optical power and efficiency [22]. As a result, many strategies aimed at improving the amount of droop utilize either an Al composition gradient [23][24][25] or a final barrier with a different thickness [23,26,27] as a workaround for this issue. In a previous study we reported high−performance green LEDs employing heterojunction−type last quantum barrier layers [28].…”
Section: Device Structure and Parametersmentioning
confidence: 99%
“…Recently, Liu et al studied the hole injection at the last quantum barrier (LQB) and p-EBL interface. By inserting an Al-composition-increasing AlGaN layer (ACI-AlGaN) between the LQB and p-EBL, the effective barrier height of holes could be reduced, and the hole accumulation could be induced in the vicinity of the n-side interface of the p-EBL, so as to promote hole injection and improve the EQE and optical power of the DUV LEDs [49].…”
Section: Improve the Hole Injection Efficiencymentioning
confidence: 99%